1989
DOI: 10.1002/j.1460-2075.1989.tb08349.x
|View full text |Cite
|
Sign up to set email alerts
|

ATP-dependent import of a lumenal protein by isolated thylakoid vesicles

Abstract: The 33 kd protein of the photosynthetic oxygen‐evolving complex is synthesized in the cytoplasm as a larger precursor and transported into the thylakoid lumen via a stromal intermediate form. In this report we describe a reconstituted system in which the later stages of this import pathway can be studied in isolation. We demonstrate import of the 33 kd protein, probably as the intermediate form, into isolated pea thylakoids by a mechanism which is stimulated by the addition of ATP. The imported protein is proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 27 publications
0
57
0
Order By: Relevance
“…Both of these proteins are nuclear-encoded and are syntheslsed with presequences consisting of two domains, a chloroplast. import domain which is removed by a peptldase located in the stroma and a thylakoid-transfer domain which is removed by a peptidase located in the thylakoid membrane [16,26], Correct cleavage of the 23 kOa polypeptide precursor by E, coil leader peptidase was confirmed by N.terminal sequencing of the processed protein [ 17]. It was also demonstrated that in vitro leader peptidase processed several precursor proteins including those for the 33 kDa and 23 kDa polypcptides both co-and post.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these proteins are nuclear-encoded and are syntheslsed with presequences consisting of two domains, a chloroplast. import domain which is removed by a peptldase located in the stroma and a thylakoid-transfer domain which is removed by a peptidase located in the thylakoid membrane [16,26], Correct cleavage of the 23 kOa polypeptide precursor by E, coil leader peptidase was confirmed by N.terminal sequencing of the processed protein [ 17]. It was also demonstrated that in vitro leader peptidase processed several precursor proteins including those for the 33 kDa and 23 kDa polypcptides both co-and post.…”
Section: Discussionmentioning
confidence: 99%
“…The necessity of Triton X-100 for extraction and in purification indicates that the enzyme is an integral or peripheral membrane protein, although the exact location in the thylakoids remains to be determined. Thylakoidal protease activities involved in protein degradation have been reported [21][22][23] and, in some cases, the enzymes have been extracted from membranes and partially purified [23]. An example of partly purified thylakoidal proteins is provided by a plastocyanin processing enzyme [23].…”
Section: Resultsmentioning
confidence: 99%
“…Thylakoidal protease activities involved in protein degradation have been reported [21][22][23] and, in some cases, the enzymes have been extracted from membranes and partially purified [23]. An example of partly purified thylakoidal proteins is provided by a plastocyanin processing enzyme [23]. This enzyme has been extracted with Triton X-100 under conditions similar to those for the D1 processing enzyme of Scenedesmus.…”
Section: Resultsmentioning
confidence: 99%
“…Although each inhibitor alone does not compromise thylakoid membrane integrity, we investigated whether they might result in vesicle lysis when present in combination, thereby exposing the stromal intermediate to the thylakoid processing peptidase located on the lumenal face of the membrane (Kirwin et al, 1989). To address this question we allowed the mature protein to accumulate in the lumen before the addition of nigericin and azide.…”
Section: The Combination Of Nigericin and Azide Does Not Cause Chloromentioning
confidence: 99%
“…There are several proteases present in the stroma that have been shown to digest imported proteins (Musgrove et al, 1989;Lindahl et al, 1996). We explored the possibility that azide might favor a nonnative conformation of iOE17, which would make it more susceptible to these proteases, thereby leading to a mature-sized proteolytic product.…”
Section: Stromal Proteases Do Not Appear To Be Responsible For the Gementioning
confidence: 99%